Iron oxide encapsulated titanium niobate nanotubes as a high-performance lithium-free anode for solid-state batteries. Issue 8 (29th January 2021) - Wu, Wei; Lin, Wang; Chen, Hongjiang; Wei, Keyan; Li, Zhitong; Yang, Haitao; Liu, Mingxian; Xiang, Huaicheng; Deng, Libo; Yao, Lei
Abstract : In the core–shell α-Fe2 O3 @TiNb2 O7 nanofiber, the high rate character of TNO and high capacity of α-Fe2 O3 work synergistically to provide enhanced specific capacity with prolonged cycle life and good rate capability, as a high performance Li-free solid-state battery anode. Abstract : The development of high-performance solid-state batteries (SSBs) that integrate high safety with high energy density has long been pursued. However, conventional lithium-containing anode materials are unable to balance these two requirements, thereby necessitating the exploration of lithium-free anodes for SSBs. In the current study, a core–shell lithium-free α-Fe2 O3 @TiNb2 O7 (TNO) nanofiber composite is synthesized and applied as an SSB anode. The confinement effect from the hollow TNO nanotubes on the encapsulated α-Fe2 O3 nanoparticles can buffer the volume-change crushing during charging/discharging, leading to robust structural stability. Moreover, the high rate capability of TNO and high capacity of α-Fe2 O3 work synergistically to provide superior electrochemical performances. The prepared α-Fe2 O3 @TNO composite delivers twice the reversible capacity (625 mA h g −1 at 0.1 A g −1 ) of pristine TNO as well as a remarkably prolonged cycle life (500 cycles with 79.2% capacity retention) and an improved rate performance (305 mA h g −1 at 3 A g −1 ) compared with those of α-Fe2 O3, making this composite the most efficient TNO-based anode material ever reported. By pairing the composite with the high-energy Li[Ni0.8 Co0.1 Mn0.1 ]O2 (NCM811) cathode, the SSB full cell exhibits a high energy density of 400 W h kg −1 . These results demonstrate the feasibility and great potential of the proposed lithium-free anode material in SSBs for practical applications.